2015
DOI: 10.1016/j.aorn.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐Assisted Thoracic Surgery (RATS): Perioperative Nursing Professional Development Program

Abstract: Robot-assisted surgery continues to grow in popularity worldwide. Competency and training of personnel for robot-assisted thoracic surgery (RATS) is less established compared with other robot-assisted specialties. Major differences between minimally invasive approaches to thoracic surgery (eg, video-assisted thoracoscopic surgery) and RATS are presented to address a paucity of literature on the subject. Although perioperative nursing considerations are universal to all robot-assisted procedures, there are nurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…For this reason, a systematic approach can be adopted that allows nurses to be prepared for robotic device errors and avoid consequences that may potentially harm the patient . In one study, it was stated that patient safety can be improved by instituting training programs for thoracic robotic surgery nurses . In the current study, it was found that nurses had insufficient information about their expected roles and that this caused stress in nurses during surgery.…”
Section: Discussionmentioning
confidence: 76%
“…For this reason, a systematic approach can be adopted that allows nurses to be prepared for robotic device errors and avoid consequences that may potentially harm the patient . In one study, it was stated that patient safety can be improved by instituting training programs for thoracic robotic surgery nurses . In the current study, it was found that nurses had insufficient information about their expected roles and that this caused stress in nurses during surgery.…”
Section: Discussionmentioning
confidence: 76%
“…the operating room, to perform the conduction process of the robot safely, knowing the function of each item, to calibrate the CO 2 insufflator in the correct pressure (21 ; to ensure the filling on the pressure points, to confirm that all the connected parts of the robot are sufficiently secured before surgery (13) ; to fit the robotic arms, understand the anatomical relations, memorize the steps of the operation (22) . Another aspect that addresses patient safety and nursing care is surgical positioning, and the authors show the importance in correctly positioning the patient (13,18,(21)(22) . A clean assessment of anatomy, guidelines, benchmarks and anatomical variations is imperative to work in synergy with the surgeon of the console and avoid positioning injury in the patient (22) .…”
Section: Resultsmentioning
confidence: 99%
“…Eleven articles approached robotic surgery in the trans/intraoperative period (A3, A4, A5, A6, A8, A9, A10, A11, A12, A13 and A15). The robot-assisted surgery continues to grow in popularity worldwide (21) .…”
Section: Transoperative/intraoperativementioning
confidence: 99%
See 2 more Smart Citations